Natural resources utilization : applications of beta-carotene and lutein extracts as natural colorants - Abu Bakar, Ainaa Eliah; Othman, Rashidi; Mat Ali, Qurratu Aini; Mohd Hatta, Farah Ayuni; Ramya, Razanah; Ab Jalil, Nurlelawati (Nova Science Publisher, Inc., 2025)
Beta-carotene and lutein are carotenoid compounds extensively applied in cosmetics, pharmaceuticals, and personal care products due to their multifunctional properties, including antioxidant activity, pigmentation, and bioactivity. Beta-carotene, a provitamin A compound, enhances skin health, visual function, and immune response, making it suitable for use in skincare, dietary supplements, and sun protection products. Lutein, a xanthophyll carotenoid, is especially valued for its photoprotective and anti-inflammatory properties, particularly in maintaining ocular and skin health. Both compounds serve as natural colourants, aligning with the global shift toward plant-based and sustainable ingredients. Technological innovations, such as encapsulation and nano-emulsions, have improved their stability and bioavailability, enabling broader applications in formulations. However, formulation challenges due to their sensitivity to heat, light, and oxidation persist. Despite this, increasing consumer demand for natural wellness solutions and preventive care supports their growing role in these industries. Future developments will enhance their functionality and broaden their impact across health and beauty sectors. © 2025 Nova Science Publishers, Inc.